Admission CT perfusion may overestimate initial infarct core: the ghost infarct core concept. (26th August 2016) - Boned, Sandra; Padroni, Marina; Rubiera, Marta; Tomasello, Alejandro; Coscojuela, Pilar; Romero, Nicolás; Muchada, Marián; Rodríguez-Luna, David; Flores, Alan; Rodríguez, Noelia; Juega, Jesús; Pagola, Jorge; et al.
Abstract : Background: Identifying infarct core on admission is essential to establish the amount of salvageable tissue and indicate reperfusion therapies. Infarct core is established on CT perfusion (CTP) as the severely hypoperfused area, however the correlation between hypoperfusion and infarct core may be time-dependent as it is not a direct indicator of tissue damage. This study aims to characterize those cases in which the admission core lesion on CTP does not reflect an infarct on follow-up imaging. Methods: We studied patients with cerebral large vessel occlusion who underwent CTP on admission but received endovascular thrombectomy based on a non-contrast CT Alberta Stroke Program Early CT Score (ASPECTS) >6. Admission infarct core was measured on initial cerebral blood volume (CBV) CTP and final infarct on follow-up CT. We defined ghost infarct core (GIC) as initial core minus final infarct >10 mL. Results: 79 patients were studied. Median National Institutes of Health Stroke Scale (NIHSS) score was 17 (11–20), median time from symptoms to CTP was 215 (87–327) min, and recanalization rate (TICI 2b–3) was 77%. Thirty patients (38%) presented with a GIC >10 mL. GIC >10 mL was associated with recanalization (TICI 2b–3: 90% vs 68%; p=0.026), admission glycemia (<185 mg/dL: 42% vs 0%; p=0.028), and time to CTP (<185 min: 51% vs >185 min: 26%; p=0.033). An adjusted logistic regression model identified time from symptom to CTP imaging <185 min as the only predictor of GIC >10 mL (OR 2.89, 95% CI 1.04 to 8.09). At 24 hours, clinical improvement was more frequent in patients with GIC >10 mL (66.6% vs 39%; p=0.017). Conclusions: CT perfusion may overestimate final infarct core, especially in the early time window. Selecting patients for reperfusion therapies based on the CTP mismatch concept may deny treatment to patients who might still benefit from reperfusion.